Cost‐effectiveness of incisional negative pressure wound therapy compared with standard care after caesarean section in obese women: a trial‐based economic evaluation. (29th December 2018) - Hyldig, N; Joergensen, JS; Wu, C; Bille, C; Vinter, CA; Sorensen, JA; Mogensen, O; Lamont, RF; Möller, S; Kruse, M
Abstract : Objective: To evaluate the cost‐effectiveness of incisional negative pressure wound therapy (iNPWT) in preventing surgical site infection in obese women after caesarean section. Design: A cost‐effectiveness analysis conducted alongside a clinical trial. Setting: Five obstetric departments in Denmark. Population: Women with a pregestational body mass index (BMI) ≥30 kg/m 2 . Method: We used data from a randomised controlled trial of 876 obese women who underwent elective or emergency caesarean section and were subsequently treated with iNPWT ( n = 432) or a standard dressing ( n = 444). Costs were estimated using data from four Danish National Databases and analysed from a healthcare perspective with a time horizon of 3 months after birth. Main outcome measures: Cost‐effectiveness based on incremental cost per surgical site infection avoided and per quality‐adjusted life‐year (QALY) gained. Results: The total healthcare costs per woman were €5793.60 for iNPWT and €5840.89 for standard dressings. Incisional NPWT was the dominant strategy because it was both less expensive and more effective; however, no statistically significant difference was found for costs or QALYs. At a willingness‐to‐pay threshold of €30, 000, the probability of the intervention being cost‐effective was 92.8%. A subgroup analysis stratifying by BMI shows that the cost saving of the intervention was mainly driven by the benefit to women with a pre‐pregnancy BMI ≥35 kg/m 2 . Conclusion: Incisional NPWT appears to be cost saving compared with standard dressings but this finding is not statistically significant. The cost savings were primarily found in women with a pre‐pregnancy BMI ≥35 kg/m 2 . Tweetable abstract: Prophylactic incisional NPWT reduces the risk of SSI after caesarean section and is probably dominant compared with standard dressings #healtheconomics. Tweetable abstract: Prophylactic incisional NPWT reduces the risk of SSI after caesarean section and is probably dominant compared with standard dressings #healtheconomics.